2021
DOI: 10.35143/jakb.v14i2.4786
|View full text |Cite
|
Sign up to set email alerts
|

STUDI EFISIENSI PASAR MODAL INDONESIA BENTUK SETENGAH KUAT PADA MASA PANDEMI COVID-19 (Perusahaan Transportasi Di Bursa Efek Indonesia Tahun 2019-2020)

Abstract: Penelitian ini bermaksud untuk menjawab bagaimanakan kondisi sektor transportasi di Indonesia pada masa pandemi covid-19. apakah sektor tersebut di pasar modal Indonesia efisien dalam bentuk setengah kuat pada masa pandemic covid-19? Metode Purposive Sampling dan Market Adjusted Model digunakan dalam pengukuran sample. Data yang digunakan adalah data abnormal return seluruh perusahaan transportasi yang terdaftar di Bursa Efek Indonesia pada periode 2019-2020 dan terdapat 35 perusahaan yang diteliti. Data diana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The resilience of capital market during the Covid-19 pandemic crisis can be observed through the normality testing of stock price movements and market variables. The results of the normality test as mentioned by Junaid et al (2021) not only reveal the stock prices distribution but also provide an overview of the extent of the company's resilience in facing Covid-19 pandemic crisis which is full of uncertainty and market fluctuations. As in the capital market normality test below (see Table 1 1 above, it is observed that the returns of food and beverage manufacturing companies are normally distributed during Covid-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…The resilience of capital market during the Covid-19 pandemic crisis can be observed through the normality testing of stock price movements and market variables. The results of the normality test as mentioned by Junaid et al (2021) not only reveal the stock prices distribution but also provide an overview of the extent of the company's resilience in facing Covid-19 pandemic crisis which is full of uncertainty and market fluctuations. As in the capital market normality test below (see Table 1 1 above, it is observed that the returns of food and beverage manufacturing companies are normally distributed during Covid-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%